Authorship Pattern of Indian Library Science Journals for the Period of 1991-2000 - Roy, Protap Chandra (Journal of Information and Knowledge, 2014)
This study is based on 1637 research papers in Library and Information Science (LIS) published in 10 Indian LIS journals during the period 1991 to 2000. The article shows that single authorship is much in vogue in LIS research work in India. Collaborative work is not much popular among the library information scientist. Here it is found that single authorship is 66.7%, two authorships is 26.45%, three authorship is 5.68%, four authorship is 0.97% and six authorship is 0.06%. So we can say that single authorship is dominating in the field of LIS research.